Digital Transformation vs COVID-19: the Case of Japan - Junzo Iida (Цифровое право, 2020)
Whilst the DX policy of the Japanese government started in 2001, then called the E-Japan Strategy and being replaced a few years later by the i-Japan Strategy, in the 20 years since then IT has not been a success in Japan’s administrative system. On the other hand, the private sector, concerned about Japan’s lagging in its adoption of information technology, has been gradually moving forward to DX measures, such as electronic contracts. Then, this year, the COVID-19 pandemic broke out. Japan is (as of July 2020) about to experience a second wave of this disease. The need for DX has become imperative in all aspects of Japanese society, especially the government and business sectors. In the first half of 2020, the government set up DX policy rapidly; for example, civil court proceedings, the traditional carve seals custom, and the submission of administrative documents to government agencies have also been forced to move forward to DX due to COVID-19. It might be said that the crisis has been the catalyst for Japan’s shift to DX. However, it will be at least a few years before it can be known whether Japan’s DX will succeed, looking at the past examples within the Japanese bureaucratic system and politicians’ attitudes towards DX.